Peran emosi dalam politik: pandangan martha nussbaum dalam kesetaraan hidup demokratis - Cicilia Damayanti (Journal of Academia Perspectives, 2021)
Nussbum said every society full of emotions. These are need for society to build up a decent country which is democratic. Her democratic society was aspiring justice and welfare. All of this can be accomplished through moral emotions, those are compassion and empathy. Imagination helps us to broaden our circle of concern for people beyond our nation. Compassion and empathy bring people far to be near, to be respected, and to be helped. For her both of these help citizens to cultivate their humanity of political justice. The justice can be reached through political liberalism, which is equal respect for citizens requires that a nation not build its political principle on any particular comprehensive doctrine of the meaning and basis of life, wheter religious or secular. Her emphazie was through education, emotions, arts, and imajination. Most of all this insight needs critical thinking. Critizining helps citizen to be active and take a part in their country. Her thought of Patriotism beyond our insight. It open our minds that we need to be wise when use this. As citizen of the world, patriotism helps us to be respectful with other citizens and country. Equality means respect for pluralism of tradition, religion, and habitus.